A new species of the genus Plumaroides Brothers (Hymenoptera: Chrysidoidea, Plumariidae) from Argentina - Diez, Patricia; Roig-Alsina, Arturo (Zootaxa, 2008)
New records of the distribution of P. andalgalensis Brothers and the description and illustration of the new species P. brothersi from San Juan and La Rioja provinces of Argentina are provided. The relationships of the two species of the genus Plumaroides Brothers are also discussed.